Estimation of the incidence of invasive meningococcal disease using a capture–recapture model based on two independent surveillance systems in Catalonia, Spain - Pilar Ciruela; Carmen Munoz-Almagro; Cristina Rius; Tomas Pumarola; Frederic Gomez-Bertomeu; Núria Soldevila; Ángela Domínguez; LAURA RUIZ; Ana Calderon; Ana Martinez; M Ángeles Domínguez; Mercé Garcia; et al. (BMJ Open)
Objectives Invasive meningococcal disease (IMD) is an urgent notifiable disease and its early notification is essential to prevent cases. The objective of the study was to assess the sensitivity of two independent surveillance systems and to estimate the incidence of IMD.Design We used capture–recapture model based on two independent surveillance systems, the statutory disease reporting (SDR) system and the microbiological reporting system (MRS) of the Public Health Agency of Catalonia, between 2011 and 2015. The capture–recapture analysis and 95% CIs were calculated using the Chapman formula. Multivariate vector generalised linear model was performed for adjusted estimation.Measures The variables collected were age, sex, year of report, size of municipality (<10 000 and ≥10 000), clinical form, death, serogroup, country of birth and type of reporting centre (private and public).Results The sensitivity of the two combined surveillance systems was 88.5% (85.0–92.0). SDR had greater sensitivity than the MRS (67.9%; 62.7–73.1 vs 64.7%; 59.4–70.0). In 2014–2015, the sensitivity of both systems was higher (80.6%; 73.2–87.9 vs 73.4%; 65.2–81.6) than in 2011–2013 (59.3%; 52.6–66.0 vs 58.3%; 51.6–65.1). In private centres, the sensitivity was higher for SDR than for MRS (100%; 100–100 vs 4.8%; −4.4–13.9). The adjusted estimate of IMD cases was lower than that obtained using the Chapman formula (279; 266–296 vs 313; 295–330). The estimated adjusted incidence of IMD was 0.7/100 000 persons-year.Conclusions The sensitivity of enhanced surveillance through the combination of two complementary sources was higher than for the sources individually. Factors associated with under-reporting in different systems should be analysed to improve IMD surveillance.